Melatonin potentiates cisplatin‐induced apoptosis and cell cycle arrest in human lung adenocarcinoma cells - Plaimee, P. (Cell Prolif, 2015)
OBJECTIVES: Melatonin produces anti‐cancer effects via several mechanisms, including by induction of apoptosis. In this way, it has been shown to be of use, in combination with chemotherapeutic drugs, for cancer treatment. The study described here has evaluated effects of melatonin on cytotoxicity, apoptosis and cell cycle arrest induced with the chemotherapeutic agent cisplatin, in human lung adenocarcinoma cisplatin‐sensitive cell line (SK‐LU‐1), which previously had only limit data. MATERIALS AND METHODS: Cells of the SK‐LU‐1 line were treated with melatonin alone at 1–5 mm concentration or cisplatin alone 10–200 μm, for 48 h in culture. Cytotoxicity was measured by MTT reduction assay. Apoptosis induction was detected by annexin V/PI staining using flow cytometric analysis and DAPI nuclear staining. Change in mitochondrial membrane potential (ΔΨm) was quantified using DiOC6(3) reagent and activities of caspases‐3/7 were also investigated. DNA fractions were measured using propidium iodide (PI) staining. RESULTS: Melatonin or cisplatin alone had 50% (IC(50)) cytotoxicity at 5 mm or 34 μm concentrations respectively. Combination of 1 or 2 mm melatonin and cisplatin significantly augmented cytotoxicity of cisplatin by reducing its IC(50) to 11 and 4 μm, respectively. Consistently, combined treatment increased population of apoptotic cells by elevating mitochondrial membrane depolarization, activating caspases‐3/7 and inducing cell cycle arrest in the S phase, compared to treatment with cisplatin alone. CONCLUSION: These data demonstrate that melatonin enhanced cisplatin‐induced cytotoxicity and apoptosis in SK‐LU‐1 lung cancer cells. SK‐LU‐1 cell population growth inhibition was mediated by cell cycle arrest in the S phase. These findings suggest that melatonin has the potential to be used for NSCLC treatment in combination with a chemotherapeutic agent such as cisplatin.